Pelaksanaan Pengawasan Parkir Liar Oleh Perusahaan Daerah (Pd) Parkir Makassar Raya - Azis, Asriyanti; Mahsyar, Abdul; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2021)
ABSTRACTThis study aimed to analyze and describe the implementation of illegal parking supervision by the local company (PD) Parking Makassar Raya. This study used qualitative research with a descriptive approach. Number of informants were 9 people and data collection techniques used observation, interview and documentation techniques. Data validation were triangulation of sources, techniques and time. Data analysis used data reduction, data presentation and conclusions. The results of this study showed that the implementation of illegal parking supervision by the Regional Company (PD) Parking Makassar Raya was good. The process of implementing supervision included Preventive and Repressive supervision between pre-implementation and post-monitoring. Preventive Supervision of the implementation of supervision at PD Parkir in terms of checking the results of target revenues and the realization of the last five years so that the PAD of parking fees had decreased, to maximize parking PAD the Parking Area Company made a breakthrough in implementing online parking, especially on potential roads on Boulevard Street. Also for the implementation of direct field supervision through Repressive Supervision, including the TRC team (Quick Reaction Team) was tasked with monitoring the whereabouts of illegal parking attendants in terms of taking action, arranging, giving directions to illegal parking attendants so as not to take illegal actions. media @HumasPD Parking.Keywords: Implementation of Preventive and Repressive Supervision